2012
DOI: 10.1183/09031936.00050211
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage as a molecular link in the pathogenesis of COPD in smokers

Abstract: In this study, we investigated whether DNA double-strand breaks (DSBs) contribute to the pathogenesis of chronic obstructive pulmonary disease (COPD).We immunofluorescence-stained lung tissue samples obtained from COPD patients, asymptomatic smokers and nonsmokers for markers of DSBs.The numbers of DSB foci (phosphorylated histone 2AX (cH2AX), phosphorylated ATM (ataxia telangiectasia mutated) substrate and phosphorylated p53-binding protein-1 foci) per cell in alveolar type I and II cells and endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 39 publications
2
97
0
Order By: Relevance
“…Many investigators, including our own group, have reported the occurrence of DNA damage (including DNA oxidation and methylation, microsatellite DNA instability, loss of heterozygosity, and DNA doublestrand breaks) in the lung tissue of COPD patients [32][33][34][35][36][37][38]. DNA breaks have also been observed in peripheral blood lymphocytes [40,43].…”
Section: Dna Damage and Sasp As A Persistent Source Of Inflammatory Mmentioning
confidence: 94%
See 2 more Smart Citations
“…Many investigators, including our own group, have reported the occurrence of DNA damage (including DNA oxidation and methylation, microsatellite DNA instability, loss of heterozygosity, and DNA doublestrand breaks) in the lung tissue of COPD patients [32][33][34][35][36][37][38]. DNA breaks have also been observed in peripheral blood lymphocytes [40,43].…”
Section: Dna Damage and Sasp As A Persistent Source Of Inflammatory Mmentioning
confidence: 94%
“…Our recent studies using human lung tissue have revealed that: 1) ROS-mediated DNA double-strand breaks not observed in control smokers can be detected in the lung tissues of COPD patients, and 2) DNA double-strand breaks not only induce apoptosis and cell senescence, but also chronic inflammation via NF-kB-dependent pro-inflammatory cytokine production by senescent cells (SASP) [38,43,45]. Similarly, AMSELLEM et al [46] showed that senescent pulmonary vascular endothelial cells produce phlogogenic substances, such as IL-6, IL-8, MCP-1 and soluble intercellular adhesion molecule-1, in COPD patients.…”
Section: Dna Damage and Sasp As A Persistent Source Of Inflammatory Mmentioning
confidence: 99%
See 1 more Smart Citation
“…[82] In certain conditions, DNA damage triggers airway inflammation, and therefore causes COPD or asthma, while on the other hand, chronic inflammation may also enhance the levels of DNA damage. Currently, anti-inflammatory treatment is still a major strategy to manage airway inflammatory diseases.…”
Section: Defects Of Dna Repair In Asthmamentioning
confidence: 99%
“…By immunofluorescence staining of these particular proteins, researchers found that alveolar type I, type II cells, and endothelial cells in patients with COPD showed higher levels of DDR at DSBs than those found in asymptomatic smokers and non-smokers. [25] Somatic DNA alterations Microsatellite DNA instability (MSI) has been correlated with a high somatic mutation rate and is associated with deficiency of DNA mismatch repair. [26,27] It was reported in 1999 that MSI was found exclusively in the sputum cells of smokers with COPD, which indicated that genetic alteration might increase susceptibility to COPD.…”
Section: Dna Dsbsmentioning
confidence: 99%